The protective effect of Eleutheroside E against the mechanical barrier dysfunction triggered by lipopolysaccharide in IPEC-J2 cells. (January 2023) - Li, Huijuan; Han, Rui; Yong, Feng; Fan, Yueli; Zhao, Bao; Hu, Xiaocai; Zhang, Tianrui; Che, Dongsheng
Abstract: Eleutheroside E (EE) exhibits immunocompetence, antioxidant, and anti-inflammatory activity. Lipopolysaccharide (LPS) can elicit a strong immune response. In vitro experiments were used to explore whether EE protects intestinal porcine jejunum epithelial cells (IPEC-J2) barriers from LPS stress. The experiment was divided into group C (control group: complete medium), group E (group C + 0.1 mg/mL EE), group L (group C + 10 μg/mL LPS), and group EL (adding 0.1 mg/mL EE for 6 h, and then adding 10 μg/mL LPS for culture). Finally, the cell proliferation, permeability, mRNA expression of cytokines, mRNA and protein expression of tight junctions (TJs) were analyzed. The result show that, when compared to the C group, EE significantly promoted the proliferation of IPEC-J2 at 58 h and showed low permeability ( P < 0.05), the anti-inflammatory cytokines IL-10 and TGF-β mRNA expression were increased extremely significantly, the inflammatory cytokines IL-6, TNF-α, and IFN-γ mRNA expression were extremely significantly decreased ( P < 0.01), the mRNA and protein expression of TJ were significantly increased in group E ( P < 0.05). However, LPS showed a damaging effect. EL group compared with L group, the cell index (CI) value was higher at 58 h ( P < 0.05), the permeability was significantly lower ( P < 0.05), the mRNA expressions of the inflammatory cytokines were down-regulated( P < 0.01), and the TJ mRNA and protein relative expression were increased ( P < 0.05). In summary, the addition of EE protects the LPS-induced increase in permeability of IPEC-J2, potentially by expressing high levels of TJ proteins and inhibiting the increase of inflammatory cytokines. Highlights: In vitro immune stress model established by LPS-induced IPEC-J2 cells. EE alleviated the inhibitory effect of LPS on IPEC-J2 cells. EE increased the protective effect on IPEC-J2 cell permeability. EE positively affects LPS-induced barrier dysfunction in IPEC-J2 cells by downregulating the expression of inflammatory cytokines.